Analisis Strategi Soar Aplikasi Sipraja Dalam mendukung Program Sidoarjo Smart City - Hakim Kubro, Febby Maulana; Arif, Lukman (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2023)
Sidoarjo Regency is ranked fourth in terms of population in East Java. The large population that continues to increase without being balanced by the availability of natural resources, facilities and infrastructure will certainly give rise to problems such as poverty, the environment, housing, health, education and so on which can reduce the quality of life of people in an urban area. Apart from that, the increase in population will also have an impact on the demand for and acceleration of public services which will also increase. To answer these challenges, Sidoarjo Regency presents an E-Gov application called SIPRAJA (Sidoarjo People's Service System) as a public service innovation from conventional to electronic while supporting the Sidoarjo Smart City program. Smart City, which is a program from the Indonesian Minister of Communication and Information, has 6 dimensions, but researchers limit the research focus to the Smart Governance dimension which has a superior program (Quick Win), namely SIPRAJA. To optimize the SIPRAJA application to support the Smart City program, various strategic efforts are needed. This research uses strategic analysis, namely SOAR analysis which maps strengths, opportunities, aspirations and results. The aim to be achieved in this research is to find out and analyze the SIPRAJA application's SOAR strategy in supporting the Sidoarjo Smart City program. This type of research uses descriptive qualitative research. The results of this research show that overall the strategy implemented by the Sidoarjo Regency Government is producing real results even though in practice there are weaknesses that need to be corrected.